Marine fungi from the Northwest African upwelling areas and from the Atlantic off Portugal - Alwin Gaertner (PANGAEA, 1982)
Quantitative data on lower marine Phycomycetes (fungi) found in the upwelling waters off the West African coast during cruises No. 13 (1968), 19 (1970), 36 (1975) and 44 (1977) of R.V. "Meteor" are reported. The distribution of the total fungi numbers is presented and, as far as possible, the evaluation of the material up to species level is given. Several provisionally named forms and groups of morphologically related, undescribed fungi are included. A correlation between the number of fungi in sediments and the water depth and distance from the coast line is postulated. There are typical distributions of the lower marine fungi in water bodies and sediments. Different values within replicates of the stations in different years show that there is a sequence in development of fungal populations induced by changes in the water bodies. Surface water far from the coast has low numbers of fungi; numbers increase to a maximum nearer to the coast. In the vicinity of the coast the values decrease. The numbers of fungi in the deep sediments are low below 1,200 m. However, there are isolated areas of higher fungal activities, indicated by some deeper grab samples. During two cruises, the "overlying water" in the grab samples was investigated. It was evident that the numbers of fungi lost by stirring of the sediment when the grab was brought up to the surface were small, relatively and absolutely. The seamount "Josephine Bank" has been investigated for the first time with respect to lower marine fungi; the populations are low in the sediments, but one sample of the surface water had a higher number than the water in the surroundings. In some hydrographic series there was a peculiar depth distribution. An increase occurred at a depth greater than 1,000 m. The results are discussed and some correlations to the aging of the fungal populations in the water masses are constructed.
Supplement to: Gaertner, A (1982): Lower marine fungi from the Northwest African upwelling areas and from the Atlantic off Portugal. Meteor Forschungsergebnisse, Deutsche Forschungsgemeinschaft, Reihe D Biologie, Gebrüder Bornträger, Berlin, Stuttgart, D34, 9-30